Application of the Upper-Bench CD Method in Super Large-Span and Shallow Tunnel: A Case Study of Letuan Tunnel - Jianxun Chen; Zilong Xu; Yanbin Luo; Jiakang Song; Weiwei Liu; Fangfang Dong (Advances in Civil Engineering)
In order to keep pace with fast urbanization and explosive growth of highway traffic volume in China, more and more super large-span tunnels are constructed or will be constructed in the coming years. It is of great significance to employ a suitable construction method for ensuring construction safety when tunnelling in a complicated geological environment. Based on the reconstruction and expansion project of Binlai in China, this paper aims at studying deformation behaviors and mechanical properties of super large-span and shallow tunnel constructed using the upper-bench CD method. The study results showed that the crown settlement of the pilot tunnel was larger than that of the rear guide tunnel, and the deformation of rock mass tended to be stable after 60 days of excavation. The structural stress changed greatly in the construction stage, the stress distribution of steel rib was mainly under compression, and the maximum compressive stress of shotcrete appeared at the tunnel vault. The supporting structure was always kept in a safe state, and its safety factor was higher than 1.5. However, the upper-bench CD method has poor performance in controlling surface subsidence and horizontal convergence. The study of this paper provides a new construction method and useful reference for similar super large-span tunnels.